Improvement of porosity of mortar using polyethylene glycol pre-polymer-impregnated mortar - Ahmed Shanaz H.; Hameed Awham M.; Al-Azawi Khalida F. (Open Engineering, 2024)
The extreme porosity and brittleness of cement mortar, when subjected to external forces, explain its fragility and low compressive and flexural resistance. Utilizing polymers is a cheap way to address these drawbacks. In this research, cement mortar samples were improved their mechanical and physical properties using the polymer-impregnated mortar (PIM) method, where polyethylene glycol (PEG) was utilized in the impregnation process through three different methods for impregnation: vacuum technique, ultrasound technique, and immersion in PEG for 24 h. The results showed an increase in mechanical properties. PIM exhibited the highest compressive strength (CS [24.47 MPa]), flexural strength (18 MPa), and splitting tensile strength (2.082 MPa) compared with the reference specimen, which attained 1.38 MPa CS, 0.52 (MPa) flexural strength, and 1.346 MPa splitting tensile strength. Optimum mechanical properties were achieved by vacuum technique, along with the increase in bulk density. The porosity test showed a slight effect of polymer on porosity. The results of diffusion showed the greater diffusivity of the reference sample compared with the PIM samples, that is, approximately 5% weight gain after one-day immersion in water. The results of thermal conductivity exhibited the increased thermal conductivity of polymer-impregnated samples compared with the reference sample.